THE ROLE OF ENGLISH IN SHAPING CULTURAL IDENTITY AMONG INDIGENOUS COMMUNITIES - Laoli, Adieli; Gulo, Neni Suryani; Gulo, Septika Novianti; Gea, Tri Yanti Nibenia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the complex dynamics of the role of English in shaping the cultural identities of indigenous peoples in various regions. This comprehensive study analyzes how contact with English influences the preservation, transformation, and negotiation of cultural identities in indigenous communities. Through a multidisciplinary approach combining ethnographic, linguistic, and anthropological methods, the study reveals the mechanisms of interaction between global languages and local cultural heritages. The findings show that indigenous peoples are not simply passive recipients of English influence, but actively adapt and redefine their identities through dynamic linguistic practices. The study highlights the complexity of the process of cultural hybridization, where English acts as a tool for negotiation, resistance, and reconstruction of identities.